Proteomic Analysis of Covalent Modifications of Tubulins by Isothiocyanates(3) - Xiao, Zhen (American Society for Nutrition, 2012)
Although isothiocyanates (ITC), which are found in cruciferous vegetables, have been shown to inhibit carcinogenesis in animal models and induce apoptosis and cell cycle arrest in tumor cells, the biochemical mechanisms of cell growth inhibition by these compounds are not fully understood. Studies have reported that ITC binding to intracellular proteins may be an important event for initiating apoptosis. Specific protein target(s) and molecular mechanisms for ITC have been investigated in human lung cancer A549 cells using proteomic tools. Cells were treated with various amounts (1–100 μmol/L) of radiolabeled phenethyl-ITC (PEITC) and sulforaphane (SFN) and the extracted proteins resolved using 2-dimensional gel electrophoresis. The results of mass spectrometric analyses suggested that tubulin may be an in vivo binding target for ITC. The binding of ITC to tubulin was associated with growth arrest. The proliferation of A549 cells was significantly reduced by ITC, with benzyl-ITC (BITC) having a greater relative activity than PEITC or SFN. Mitotic arrest and apoptosis as well as disruption of microtubule polymerization were induced in the order: BITC > PEITC > SFN. An analysis of tubulins isolated from BITC-treated A549 cells showed that Cys(347), a conserved cysteine in all α-tubulin isoforms, was covalently modified by BITC. Taken together, these results suggest that tubulin is a binding target of ITC and that this interaction can lead to growth inhibition and apoptosis.